If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = y Solving 7 + -3x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = -7 + y Combine like terms: 7 + -7 = 0 0 + -3x = -7 + y -3x = -7 + y Divide each side by '-3'. x = 2.333333333 + -0.3333333333y Simplifying x = 2.333333333 + -0.3333333333y
| 2345x-23167=3 | | 747-60x=147 | | 25z+5-8=147 | | 0.4-1.2=0.3r+0.6 | | 8q=32 | | 7(-2x+10)=42 | | 8(2-5x)=-264 | | 11.3+-7.2=3.82 | | 747-60x=0 | | 4y+5(5+y)=-2 | | ax+by=0 | | 2(-4r+2)=-6(-8+2r) | | .53y+2.5=5.1 | | -88+9z=z | | 3xz+4-8=1 | | 2(4d+5h)-(9h-5d)= | | 2x+1+4x+4=4 | | 7u-22=-1 | | -8(6x+5)=-520 | | 4h+7=4h | | x+3=30 | | 220+0.15x=368.50 | | (3x^2y+7xy^2)(x^2y^3-2y^2)= | | 11=1+8m+2n | | -5x-10=2-(x-4) | | 3(2+e)-4e=e+16 | | 9.1x+23.1=-4.2 | | (5x^5y^4)(2x^5y)= | | 21b=-19 | | 7(4x-2)=322 | | 112=4x+6(x+7) | | 5x-5=33 |